THE IMPACT OF IMPLEMENTING DIGITALIZATION IN THE FIELD OF INTERNAL AUDIT IN THE CONTEXT OF THE INCREASING COMPLEXITY OF THE SOCIO-ECONOMIC ENVIRONMENT IN THE AGRICULTURAL FIELD - Dorina MOCUTA; Doina Maria TILEA; Cristina BALACEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article analyzes how the use of information technologies to analyze internal audit information can generate added value for agricultural companies. With the help of audit tests performed using audit applications (risk alerts, support for different data formats, customized forms, verification of quantitative or qualitative elements), audit specialists will contribute to the development of governance systems of agricultural companies in the sense that, by digitizing reports, they will have the possibility to analyze recommendations, track the flow of documents and the tools used by the audit team. The research method chosen was the use of a questionnaire consisting of 12 questions/items, addressed to internal auditors working the level of companies whose main activity is agriculture. Through the research activity undertaken, the need for internal audit to become a digitalized work tool was emphasized, which would provide stakeholders with documents in the form of reports that converge with the principles of participatory management, risk management, and governance, which would constitute the premises for an investigative audit.